An outbreak following importation of wild poliovirus in Xinjiang Uyghur Autonomous Region, China, 2011 - Wang, Hai-Bo (BMC Infect Dis, 2015)
BACKGROUND: After more than 10 years without a case of wild poliovirus (WPV) in China, an outbreak occurred in 2011 in Xinjiang Uyghur Autonomous Region. METHODS: Acute flaccid paralysis (AFP) case surveillance was strengthened with epidemiological investigations and specimen collection and serological surveys were conducted among hospitalized patients. RESULTS: There were 21 WPV cases and 23 clinical compatible polio cases reported. WPV was isolated from 14 contacts of AFP cases and 13 in the healthy population. Incidence of WPV and clinical compatible polio cases were both highest among children <1 years, however, 24/44 (54.5%) polio cases were reported among adults aged 15–39 years. CONCLUSIONS: High coverage of routine immunization should be maintained among children until WPV transmission is globally eradicated. Expansion of AFP case surveillance and use of serologic surveys to estimate population immunity should be conducted rapidly to guide preparedness and response planning for future WPV outbreaks.